2021
DOI: 10.1186/s12894-021-00902-8
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of urine microvesicles from prostate cancer patients: different approaches, different visions

Abstract: Background Because of their specific and biologically relevant cargo, urine extracellular vesicles (EVs) constitute a valuable source of potential non-invasive biomarkers that could support the clinical decision-making to improve the management of prostate cancer (PCa) patients. Different EV isolation methods differ in terms of complexity and yield, conditioning, as consequence, the analytical result. Methods The aim of this study was to compare th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Obviously, this represents a problem for study comparisons, even if reporting guidelines now help to identify differences, facilitate replication and/or explain the lack of it [12,172]. Prior studies have explored the effect of uEV isolation workflows on uEV RNA sequencing profiles focusing on miRNA sequencing [15,[20][21][22]. We have previously demonstrated that the uEV isolation workflow (UC, HFD and NG) has a surprisingly variable impact on the miRNA and mRNA profiles [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, this represents a problem for study comparisons, even if reporting guidelines now help to identify differences, facilitate replication and/or explain the lack of it [12,172]. Prior studies have explored the effect of uEV isolation workflows on uEV RNA sequencing profiles focusing on miRNA sequencing [15,[20][21][22]. We have previously demonstrated that the uEV isolation workflow (UC, HFD and NG) has a surprisingly variable impact on the miRNA and mRNA profiles [13].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, only few studies have characterized the effect of pre-analytical variables on the uEV, especially regarding the end-point biomolecular level used in biomarker studies, e.g., the transcriptome [14]. Equally, only a few studies have comprehensively characterized the effect of EV isolation methods on transcriptomics [13,15,16,[20][21][22]. Thus, it is difficult to compare results between dissimilar studies.…”
Section: Introductionmentioning
confidence: 99%
“…A study successfully isolated sEVs from normal prostate RWPE1 cells using ultrafiltration and characterized their associated proteins [ 37 ]. Another study found that SEC demonstrated advantages of high purity and low protein contamination in the extraction of sEVs from the plasma and urine of PCa patients, ensuring the quality requirements for subsequent downstream analysis [ 38 , 39 ]. Chen et al developed a highly efficient sEV isolation platform called Exosome detection via the ultrafast-isolation system (EXDUS) that is based on ultrafiltration, which achieves ultrafast and efficient purification of sEVs through negative pressure oscillation and double-coupled harmonic oscillator-enabled membrane vibration.…”
Section: Sev Isolation and Characterizationmentioning
confidence: 99%
“…EVs carry DNA, RNA, microRNA (miRNA), proteins and lipids, which play important roles in intercellular communication, which modulates and regulates adjacent recipient cells. Exosomes have been found in physiologic fluids such as bronchoalveolar lavage [2], serum [3,4], urine [5] and are most abundant in human milk [6], as well as in bovine, yak, goat and porcine sources [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%